ANALISIS YURIDIS PEMBATALAN PERJANJIAN PERDAMAIAN (HOMOLOGASI) PERKARA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG PADA PENGADILAN NIAGA - Kalundas, Syamsu; Kurnia, Mahendra Putra; Fauzi, M (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This research will highlight and analyze the cancellation of the peace agreement in the PKPU case based on Supreme Court (MA) Decision No. 667 K/pdt.sus-pailit/2021. This decision attracted attention because the Supreme Court canceled the Peace Agreement (Homologation) between creditors and debtors which was issued after the Creditor was declared Bankrupt, so it is necessary to deepen and analyze the application of the regulations and the judge's considerations in deciding the case, so this is an interesting matter for the writer to discuss, and An analysis of the bankruptcy entry route will be carried out based on the provisions of Chapters II and III of the Bankruptcy Law and PKPU. In this case, there are decisions that contradict one another. This type of research is normative legal research. Normative legal research is research carried out by analyzing written law from library materials or mere secondary data, better known as secondary legal materials and reference materials in the legal field or reference materials in the legal field. Research Approach. Decision in the context of the PT Hanson International Tbk case. shows the complexity between legal idealism (sollen), namely as contained in Law Number 37 of 2004 Article 228 paragraph (6) which regulates the number of extensions, namely 270 days, and the reality (sein) contained in Cassation Decision No. 667 K/pdt.sus-pailit/2021. Although